Điều tra cơ bản dân tộc Cống - Báo cáo chuyên đề - Nguyễn, Minh Duy (2011)
Tác giả: Nguyễn Minh Duy, ThS; Nguyễn Quang Vinh, KS; Ma Thế Luận, BS; Mai Thị Quy, CN; và những người khác -- Từ khóa: Dân tộc Cống; Dân tộc ít người